RESISTÊNCIA AOS ANTIMICROBIANOS E ANÁLISE DA DIVERSIDADE GENÉTICA DE STAPHYLOCOCCUS AUREUS POR PCR-RAPD - Neves, M.c. [UNESP]; Costa, J.r.v. [UNESP]; Vieira, V.c. [UNESP]; Abreu, I.l. [UNESP]; Lemos, M.v.f [UNESP] (Instituto Biológico, 2021)
The aim of this study was to analyze in vitro antimicrobial susceptibility of Staphylococcus aureus strains isolated from teats of cow udders and milking workers’ hands as well as to verify polymorphism among them by using RAPD-PCR technique. Tests were conducted by disk diffusion technique and after the collection of the genetic material PCR and RAPD techniques were performed with the use of 40 different initiators. The analysis of polymorphism was conducted by using the NTSYS program of numerical taxonomy. The susceptibility of antimicrobials in the strains collected from teats of cow udders was 4% to penicillin, 88% to tetracycline, 92% to gentamicine, 96% to vancomycin and 100% to chloranfenicol. As for the strains collected from milking workers’ hands, susceptibility results were 0% to penicillin, 70% to tetracycline and 90% to vancomycin and 100% to gentamicine and chloranfenicol antimicrobials. E-test showed minimum inhibitory concentration (MIC) greater than 256 ?g/mL to strains resistant to the antimicrobial vancomycin. The studies made it possible to detect S. aureus resistance upon the use of the tested antimicrobials and to determine the genetic diversity found among strains of staphylococcus due to the presence of many polymorphic bands found in all initiators.

O objetivo deste trabalho foi analisar a sensibilidade antimicrobiana in vitro de cepas de Staphylococcus aureusisoladas de tetos de vacas e mãos de retireiros, além de verificar o polimorfismo entre elas pela técnica de PCR-RAPD. Os testes foram realizados pela técnica de difusão em discos e, após a extração do material genético foram desenvolvidas as técnicas de PCR e RAPD, usando para isso 40 iniciadores diferentes. A análise do polimorfismo foi realizada empregando-se o programa de taxonomia numérica NTSYS. As sensibilidades dos antimicrobianos nas cepas obtidas de tetos de vacas foram 4% para a penicilina, 88% para a tetraciclina, 92% para a gentamicina, 96% para a vancomicina e 100% ao cloranfenicol. Para as cepas provenientes das mãos de retireiros, os resultados de sensibilidade foram zero para a penicilina, 70% para a tetraciclina e 90% para a vancomicina e 100% para os antimicrobianos gentamicina e cloranfenicol. A realização do E-teste indicou uma concentração inibitória mínima (CIM) maior que 256 mg/mL para as cepas resistentes ao antimicrobiano vancomicina. Os estudos permitiram detectar a resistência dos S. aureus mediante o uso dos antimicrobianos testados e determinar a diversidade genética entre as cepas de estafilococos devido à presença de muitas bandas polimórficas encontradas em todos os iniciadores.
RESISTANCE TO ANTIMICROBIALS AND ANALYSIS OF STAPHYLOCOCCUS AUREUS GENETIC DIVERSITY USING RAPD-PCR
Keywords: Antimicrobial resistance; dairy cattle; polymorphism; Resistência antimicrobiana; vacas leiteiras; polimorfismo